Metode Tanya Diskusi dalam Pembelajaran Al-Qur’an Hadist di MAN 3 Siabu - Kholidah Nur; Muniroh Ainun Basaroh; Winda Anwari Siregar; Nasli Agusti Sikumbang; Uci Purnama; Meidi (PT. Willy Print Art, 2025)
This study aims to describe the implementation of the discussion method in learning Al-Qur’an Hadith at MAN 3 Siabu and to analyze its effectiveness in enhancing students’ activeness and comprehension. This research employed a qualitative approach with a field research design and descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students. The findings indicate that the discussion method significantly improves student participation, conceptual understanding, and critical thinking skills. Various forms of discussion, including group discussions, class discussions, and debates, were utilized to create an interactive learning environment. Students responded positively to the application of this method, showing increased enthusiasm in asking questions, presenting arguments, and delivering group results. Supporting studies from previous research also confirm that the discussion method effectively enhances learning outcomes, motivation, and analytical skills in both Al-Qur’an Hadith learning and classical Islamic texts. Challenges such as passive students were addressed through proper classroom management and teacher facilitation. Overall, the discussion method proves to be highly relevant and effective in improving the quality of Al-Qur’an Hadith learning.